A Qualitative Study To Explore the Impact of Having Children with Cancer and Parental Adjustment - Nurhidayah, Ikeu; Nurhaeni, Nani; Allenidekania, Allenidekania; Gayatri, Dewi; Hendrawati, Sri (http://dharmais.co.id/, 2024)
Background: Cancer diagnosis in children impacts not only the children themselves but also their parents, and the role of providing support during the treatment process is crucial. The illness’s complexity, the diagnosis process, and the course of treatment can have various effects on parents and family life. To cope with the challenges of caring for their chronically ill children, families adopt a normalization process to restore their routines. Therefore, this study aims to investigate the implications of a childhood cancer diagnosis on families and how parents normalize their daily lives in the face of this difficult situation. Methods: The study was a qualitative study conducted in a pediatric cancer shelter house in Bandung, Indonesia, from May to August 2018. Ten parents who had children with cancer were included in the study. Data were collected through interviews and thematically analyzed. Results: This study yielded five themes: 1) parents’ negative feelings when children are first diagnosed with the illness, 2) various changes in the family’s life, 3) the impact on the family’s quality of life, 4) family’s extra effort to overcome the illness’s impact and 5) parents’ expectations for social support. Conclusions: Cancer in children has a significant impact on the lives of the entire family, particularly parents. Normalizing the lives of parents who have children with cancer entails several adaptation or adjustment tasks. Nurses can assist families in adapting by guiding how to deal with the changes they are experiencing and accepting this as the new normal. Nurses can help families normalize their daily routines, provide social support, improve coping strategies, increase family closeness, and identify the source of support from other families or the community.